IbM GURU-GURU PAUD DI KECAMATAN PRINGAPUS KABUPATEN SEMARANG - Sinta Wardani; Pipit Mugi Handayani; Siti Ulfiyani (E-Dimas: Jurnal Pengabdian kepada Masyarakat, 2015)
Abstract Cases of violence against children are prevalent recently. The actors of physical or verbal violence against children is not only adults, but also conducted by peers who are still in early age. Children certainly do not do it because they want to, they tend to do so because they imitate what they has seen and heard from their social environment. This kind of violence sparked fears for early childhood teachers in District Pringapus, Semarang regency. This concern relates to the way teachers respond impolite language or verbal abuse committed and experienced by children as it relates to the character education of children. This training is intended to equip teachers to establish verbal communicators who are humane and away from violence in communicating with children. The material presented includes child psychology, politeness and non-violence in the realm of education, interaction in teaching and learning, and character education. The material is presented with lecture, discussion, and assignment. Community service activities in form of training gain a positive response from the participants. Keywords: verbal, language politeness, character education